2021
DOI: 10.1177/25161032211001078
|View full text |Cite
|
Sign up to set email alerts
|

Responding to COVID-19’s impact on supervised family time: The supportive virtual family time model

Abstract: COVID-19 has put child wellbeing at risk, perhaps especially, for children and youth involved in the foster care system. For these children and youth, any stability they may have experienced since entering care has been disrupted and their contact with parents limited. A sudden shift to virtual only contact meant both parents and caregivers were in need of support to navigate these changes. This study reports on the rapid development and implementation of an eLearning and structured practice guide for visitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Because in-person visits are not always possible, it is equally as important to ensure that child welfare workers and foster parents receive the necessary training and guidance to ensure cooperative and collaborative relationships between foster parents and families of origin, as well as support in coping with the technology challenges that are common in virtual communication (Orlando et al, 2021). Further, social service departments can facilitate access to computers at county facilities and/or stable internet connections as a way of helping parents of origins and foster parents who are disproportionately affected due to their economic constraints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because in-person visits are not always possible, it is equally as important to ensure that child welfare workers and foster parents receive the necessary training and guidance to ensure cooperative and collaborative relationships between foster parents and families of origin, as well as support in coping with the technology challenges that are common in virtual communication (Orlando et al, 2021). Further, social service departments can facilitate access to computers at county facilities and/or stable internet connections as a way of helping parents of origins and foster parents who are disproportionately affected due to their economic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Amidst COVID-19, family time has been challenged due to state and agency rules and guidelines related to physical distancing and other virus mitigation strategies. Virtual contact has, in some locations and/or at certain points during the COVID-19 pandemic, been the only available option to support continued family visitation (Orlando et al, 2021). A survey of 197 child welfare professionals, birth parents, adoptive parents, and foster parents in the United Kingdom during the early part of the COVID-19 pandemic found that face-to-face contact had all but ceased and in most cases was replaced by video communication and other forms of electronically mediated contact (Neil et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also compared universities in the Philippines, Thailand, Vietnam, and Indonesia (Joaquin et al, 2020). Another model is a training and mentoring model in the home to support online learning (Orlando et al, 2021). Studies of students' perception of online learning in pandemic times show many obstacles and are ineffective (Purwadi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Children and parents in Child Protective Services (CPS) are considered the most vulnerable in this pandemic ( Bolborici, 2020 ; Fegert & Schulze, 2020 ; Frimpong-Manso et al, 2021 ; Goldberg, Brodzinsky, Singer, & Crozier, 2021 ; Goldberg, McCormick, & Virginia, 2021 ; Janssen et al, 2020 ; Langley, Ruderman, Waterman, & Franke, 2021 ; Orlando et al, 2021 ) as the majority families in CPS tend to have ongoing needs (see Caldwell et al, 2020 ). Several scholars believe that the vulnerability of children and families in need has intensified in this global crisis ( Bolborici, 2020 ; Franic & Dodig-Curkovic, 2020 ; Vilar-Compte, Pérez, Teruel, Alonso, & Pérez-Escamilla, 2020 ; Zhang, Li, Shi, Dong, & Wang, 2021 ).…”
mentioning
confidence: 99%